Detection of cerebral amyloid angiopathy by 3‐T magnetic resonance imaging and amyloid positron emission tomography in a patient with subcortical ischaemic vascular dementia. Issue 1 (18th January 2016) - Kida, Hirotaka; Satoh, Masayuki; Ii, Yuichiro; Fukuyama, Hidenao; Maeda, Masayuki; Tomimoto, Hidekazu
Abstract: The patient was an 81‐year‐old man who had been treated for hypertension for several decades. In 2012, he developed gait disturbance and mild amnesia. One year later, his gait disturbance worsened, and he developed urinary incontinence. Conventional brain magnetic resonance imaging using T2 ‐weighted images and fluid‐attenuated inversion recovery showed multiple lacunar infarctions. These findings fulfilled the diagnostic criteria for subcortical ischaemic vascular dementia. However, susceptibility weighted imaging showed multiple lobar microbleeds in the bilateral occipitoparietal lobes, and double inversion recovery and 3‐D fluid‐attenuated inversion recovery images on 3‐T magnetic resonance imaging revealed cortical microinfarctions in the left parietal‐temporo‐occipito region. Pittsburgh compound B‐positron emission tomography revealed diffuse uptake in the cerebral cortex. Therefore, we diagnosed the patient with subcortical ischaemic vascular dementia associated with Alzheimer's disease. The use of the double inversion recovery and susceptibility weighted imaging on 3‐T magnetic resonance imaging may be a supplemental strategy for diagnosing cerebral amyloid angiopathy, which is closely associated with Alzheimer's disease.